Normal Expiratory Flow Rate and Lung Volumes in Patients with Combined Emphysema and Interstitial Lung Disease: A Case Series and Literature Review - Karen L Heathcote; Donald W Cockcroft; Derek A Fladeland; Mark E Fenton (Canadian Respiratory Journal)
Pulmonary function tests in patients with idiopathic pulmonary fibrosis characteristically show a restrictive pattern including small lung volumes and increased expiratory flow rates resulting from a reduction in pulmonary compliance due to diffuse fibrosis. Conversely, an obstructive pattern with hyperinflation results in emphysema by loss of elastic recoil, expiratory collapse of the peripheral airways and air trapping. When the diseases coexist, pulmonary volumes are compensated, and a smaller than expected reduction or even normal lung volumes can be found. The present report describes 10 patients with progressive breathlessness, three of whom experienced severe limitation in their quality of life. All patients showed lung interstitial involvement and emphysema on computed tomography scan of the chest. The 10 patients showed normal spirometry and lung volumes with severe compromise of gas exchange. Normal lung volumes do not exclude diagnosis of idiopathic pulmonary fibrosis in patients with concomitant emphysema. The relatively preserved lung volumes may underestimate the severity of idiopathic pulmonary fibrosis and attenuate its effects on lung function parameters.